2002
DOI: 10.1097/00007435-200209000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use Errors and Problems Among College Men

Abstract: Condom use errors were common, and error scores were associated with breakage and slippage. Increasing the focus on correcting potential user failures may be an important public health strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 23 publications
7
95
2
Order By: Relevance
“…The questionnaire was a slightly modified version of an instrument used in similar studies of condom use errors and problems among university students. [10][11][12] We used a 3-month recall period. We assessed discomfort using the following survey question: "In the past 3 months did you or your partner have problems with the way a condom fit or felt (for example, the condom was too large or too small, it was the wrong shape, it caused irritation of your skin or genitals or your partner's genitals, it caused loss of erotic sensation for you or your partner)?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was a slightly modified version of an instrument used in similar studies of condom use errors and problems among university students. [10][11][12] We used a 3-month recall period. We assessed discomfort using the following survey question: "In the past 3 months did you or your partner have problems with the way a condom fit or felt (for example, the condom was too large or too small, it was the wrong shape, it caused irritation of your skin or genitals or your partner's genitals, it caused loss of erotic sensation for you or your partner)?…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] A few studies have addressed a broader array of issues, including incorrect application of condoms, incomplete use of condoms, and erection problems associated with condom use. [8][9][10][11][12] One potentially important aspect of individuals' experiences with condoms, however, has not been sufficiently addressed by previous research: discomfort associated with condom use.…”
mentioning
confidence: 99%
“…5 Two sexual behaviors are driving the heterosexual HIV epidemic propagation in the USA: unprotected vaginal or anal sex 6,7 and concurrent partnering. [8][9][10] Several factors have been found to reduce consistent condom use among heterosexual men regardless of race/ethnicity, including reduced sexual pleasure and concerns about sexual performance, [11][12][13] negative outcome expectancies, 14,15 condom use selfefficacy, [16][17][18][19] attitudes towards condoms, 13,17,19 and risk perceptions. [20][21][22] Condom use also varies by partnership type, 23 relationship duration, 24,25 use of other contraceptive methods, 26,27 and sexual communication, [28][29][30][31] as well as drug and alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although much of this research has been descriptive, few studies have identified likely causes of these problems. 5,7,8,14 For example, allowing condoms to contact sharp objects, reporting problems with 'fit-and-feel' condoms and having low self-efficacy to use condoms correctly may predispose men to experience condom breakage.…”
Section: Introductionmentioning
confidence: 99%